Exploring Phytochemicals of Traditional Medicinal Plants Exhibiting Inhibitory Activity Against Main Protease, Spike Glycoprotein, RNA-dependent RNA Polymerase and Non-Structural Proteins of SARS-CoV-2 Through Virtual Screening - Nallusamy, Saranya; Mannu, Jayakanthan; Ravikumar, Caroline; Angamuthu, Kandavelmani; Nathan, Bharathi; Nachimuthu, Kumaravadivel; Ramasamy, Gnanam; Muthurajan, Raveendran; Subbarayalu, Mohankumar; Neelakandan, Kumar (Frontiers in Pharmacology, 2021)
Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) being a causative agent for global pandemic disease nCOVID’19, has acquired much scientific attention for the development of effective vaccines and drugs. Several attempts have been made to explore repurposing existing drugs known for their anti-viral activities, and test the traditional herbal medicines known for their health benefiting and immune-boosting activity against SARS-CoV-2. In this study, efforts were made to examine the potential of 605 phytochemicals from 37 plant species (of which 14 plants were endemic to India) and 139 antiviral molecules (Pubchem and Drug bank) in inhibiting SARS-CoV-2 multiple protein targets through a virtual screening approach. Results of our experiments revealed that SARS-CoV-2 MPro shared significant dissimil4arities against SARS-CoV MPro and MERS-CoV MPro indicating the need for discovering novel drugs. This study has screened the phytochemical cyanin (Zingiber officinale) which may exhibit broad-spectrum inhibitory activity against main proteases of SARS-CoV-2, SARS COV) and MERS CoV) with binding energies of (-) 8.3 kcal/mol, (-) 8.2 kcal/mol and (-) 7.7 kcal/mol respectively. Amentoflavone, agathisflavone, catechin-7-o-gallate and chlorogenin were shown to exhibit multi-target inhibitory activity. Further, Mangifera indica, Anacardium occidentale, Vitex negundo, Solanum nigrum, Pedalium murex, Terminalia chebula, Azadirachta indica, Cissus quadrangularis, Clerodendrum serratum and Ocimum basilicumaree reported as potential sources of phytochemicals for combating nCOVID’19. More interestingly, this study has highlighted the anti-viral properties of the traditional herbal formulation “Kabasura kudineer” recommended by AYUSH, a unit of Government of India. Short listed phytochemicals could be used as leads for future drug design and development. Genomic analysis of identified herbal plants will help in unravelling molecular complexity of therapeutic and anti-viral properties which proffer lot of chance in the pharmaceutical field for researchers to scout new drugs in drug discovery.